ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕГИ ИНСАН ИНТЕЛЛЕКТУАЛ ҲӘРЕКЕТИН ВЕРБАЛЛАСТЫРЫЎШЫ ФРАЗЕОЛОГИЯЛЫҚ БИРЛИКЛЕРДИҢ СТРУКТУР-СЕМАНТИКАЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Бердамбетова, А.П. (FAN va JAMIYAT, 2023)
This article is about the features of verbalization in all national forms, in which the phraseological system is reborn in the conditions of additional anthropocentrism, that is, on the basis of the origin and movement of phraseological units.